Where You Live Matters: Structural Correlates of HIV Risk Behavior Among Young Men Who Have Sex with Men in Metro Detroit. - Bauermeister, José A; Eaton, Lisa; Andrzejewski, Jack; Loveluck, Jimena; VanHemert, William; Pingel, Emily S (AIDS and behavior, 2015)
Structural characteristics are linked to HIV/STI risks, yet few studies have examined the mechanisms through which structural characteristics influence the HIV/STI risk of young men who have sex with men (YMSM). Using data from a cross-sectional survey of YMSM (ages 18-29) living in Detroit Metro (N = 328; 9 % HIV-positive; 49 % Black, 27 % White, 15 % Latino, 9 % Other race), we used multilevel modeling to examine the association between community-level characteristics (e.g., socioeconomic disadvantage; distance to LGBT-affirming institutions) and YMSM's HIV testing behavior and likelihood of engaging in unprotected anal intercourse with serodiscordant partner(s). We accounted for individual-level factors (race/ethnicity, poverty, homelessness, alcohol and marijuana use) and contextual factors (community acceptance and stigma regarding same-sex sexuality). YMSM in neighborhoods with greater disadvantage and nearer to an AIDS Service Organization were more likely to have tested for HIV and less likely to report serodiscordant partners. Community acceptance was associated with having tested for HIV. Efforts to address YMSM's exposure to structural barriers in Detroit Metro are needed to inform HIV prevention strategies from a socioecological perspective.